Business-to-Business International New Ventures: Building Brand Awareness Globally Through Entrepreneurial Digital Marketing - Macháčová, Petra (My University, 2019)
The increasing number of organizations that are international from their inception, also known as International New Ventures (INVs), has become an emerging phenomenon and gained a great interest in research for over the last few decades. Existing studies have partially explained the range of required capabilities that are needed for a smooth internationalisation of INVs, nonetheless, the importance of branding has been a rather scarce research area. Therefore, this research strives to fill in the research gap and focuses on the research question dealing with the fact how INVs that are operating in B2B high-tech markets build up their global brand awareness in the internationalisation process through entrepreneurial digital marketing. Accordingly, three research objectives are formulated in order to answer the research question. Firstly, to develop the dimensions of entrepreneurial digital marketing strategies suitable for international markets. Secondly, to create a theoretical framework explaining how B2B INVs build their brand awareness during internationalisation, including factors that are influencing this development. Thirdly, to identify the practices that are adopted by B2B INVs while utilisation of entrepreneurial digital marketing for building brand awareness globally. The empirical part of this study was using a qualitative research method and four Finnish INVs from B2B high-tech markets were selected as sample. The primary data were mainly collected through semi-structured interviews with founders and managers from selected companies. Based on the empirical results, it is proposed that implementation of an entrepreneurial digital marketing approach contributes to the global brand awareness which consequently helps with the internationalisation process of the newly established international enterprises. Moreover, INVs that utilise entrepreneurial digital marketing dimensions as innovativeness, proactive opportunity-seeking and customer-focus are expected to build a stronger brand than companies without this approach.
Keywords: International New Ventures; International Branding; International entrepreneurship; International entrepreneurial marketing; Entrepreneurial digital marketing; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|